2022
DOI: 10.18287/2412-6179-co-1098
|View full text |Cite
|
Sign up to set email alerts
|

An automatic method for subpixel registration of KMSS-M imagery based on coarse-resolution actualized reference

Abstract: The paper describes a method for automatic subpixel-accurate geographic referencing of imagery acquired by KMSS-M with 60 m spatial resolution, based on leveraging a coarse, reconstructed, cloud-free and daily updated MODIS surface reflectance reference image. The method is based on maximizing Pearson's correlation value when determining an optimal local displacement of the distorted image fragment by comparing with the reference image. To assess the effectiveness of the method when used over continental-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The resultant mean absolute error of geolocation for all qualified nodes processed over the Russian grain belt does not exceed 40 meters for KMSS imagery acquired during the season of 2020, as was shown earlier [33] using Sentinel-2 (MSI) imagery as a reference. It was also shown that geolocation misalignments between source KMSS and reference Sentinel-2 imagery are not uncommon to exceed 3000 meters.…”
Section: Kmss Data Processingsupporting
confidence: 66%
See 2 more Smart Citations
“…The resultant mean absolute error of geolocation for all qualified nodes processed over the Russian grain belt does not exceed 40 meters for KMSS imagery acquired during the season of 2020, as was shown earlier [33] using Sentinel-2 (MSI) imagery as a reference. It was also shown that geolocation misalignments between source KMSS and reference Sentinel-2 imagery are not uncommon to exceed 3000 meters.…”
Section: Kmss Data Processingsupporting
confidence: 66%
“…It was also indicated that LOWESS-reconstructed MODIS reference imagery features higher geolocation accuracy than the original MOD09 datasets. Namely, using Sentinel-2 (MSI) imagery of decameter resolution as a reference, it was shown that the average geolocation error of LOWESS-reconstructed MODIS was below 20 m [33], making these MODIS images suitable for sub-pixel KMSS imagery georeferencing.…”
Section: Modis Data Processingmentioning
confidence: 99%
See 1 more Smart Citation